2021
DOI: 10.1111/ijcs.12639
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of household norms for energy efficient behavior

Abstract: Household norms have been shown to influence energy efficiency behaviors, but little is known about the relative influence of household norms when compared to other established drivers of household efficiency behaviors, such as comfort‐seeking, environmental concern and cost sensitivity. This paper unpacks the nature of the influence of household norms on household efficiency behaviors, whether as antecedents, mediating the influence of other drivers or a direct influence on efficiency behaviors. Responses fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The actions that are quite obvious, and often used by households especially in conditions of rising energy prices, do not depend directly on environmental awareness but rather on price factors and likely on the desire to save money, as pointed out, e.g., by Kleinschafer et al [61] and Sharma, Kaura, and Syan [12].…”
Section: Hypothesis Decisionmentioning
confidence: 99%
“…The actions that are quite obvious, and often used by households especially in conditions of rising energy prices, do not depend directly on environmental awareness but rather on price factors and likely on the desire to save money, as pointed out, e.g., by Kleinschafer et al [61] and Sharma, Kaura, and Syan [12].…”
Section: Hypothesis Decisionmentioning
confidence: 99%
“…Indeed, in conversations with consumers actively seeking ways to save energy at home, we heard of the inspiring example of a mother, who having interacted with other consumers online, invented a game (Power Rangers) in which her children enjoyed competing to see who could identify the most ways to save energy. This was an innovative and motivating way to engage children in energy-saving behavior, which supported the internalization of energy saving values and the potential establishment of household norms (Kleinschafer et al, 2020). Other examples of consumers working together with other consumers to save energy can be witnessed in a variety of neighborhood initiatives, many of which build on induced competition (Swann, 2019) and social norm message development (Burchell et al, 2016).…”
Section: Integrated Regulation -Environmental Considerationsmentioning
confidence: 96%
“…Based on these sub-theories, VBN theory of Stern et al (1999) and Stern (2000) Various studies on sustainable behaviors of consumers have shown the relationships among these aforementioned constructs of VBN, such as environmental concern (Bamberg, 2003;Choi & Kim, 2005;Landon et al, 2018;Sharma, 2021), different types of values (De Groot & Steg, 2008;Follows & Jobber, 2000;Fraj & Martinez, 2006;Gärling et al, 2003;Landon et al, 2018;Nordlund & Garvill, 2002;Taufique, 2022), environmental consequences (Follows & Jobber, 2000), and different types of norms (Corbett, 2005;Kleinschafer et al, 2021;Lopes et al, 2019;Nordlund & Garvill, 2002). These moral-focus theory-based studies, however, do not cover behavioral intention, which is considered as the immediate antecedent of actual behavior.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Over the last few decades, sustainable consumption has become a research interest of many scholars (e.g., Carrington et al, 2010; Hosta & Zabkar, 2021; Lee et al, 2014; Longo et al, 2019; Nguyen & Johnson, 2020; Onel & Mukherjee, 2015; Schuitema & De Groot, 2015; White et al, 2019). Although such behaviors pertain to all aspects of human consumption, such as purchase, usage, and disposal, consumer behavior studies in the literature typically pay attention to only one type of behavior, such as recycling (Best & Mayerl, 2013; Tonglet et al, 2004), household energy use (Abrahamse & Steg, 2011; Kleinschafer et al, 2021), sustainable travelling (Caruana et al, 2020; Flores & Jansson, 2021), purchase (Barbarossa & De Pelsmacker, 2016; Dagher & Itani, 2014; Paul & Rana, 2012; Sharma, 2021; Steg & Vlek, 2009), and sustainable food consumption (Tekinbaş Özkaya et al, 2021). Also, even though Gatersleben et al (2002), Stern (2000) and Steg and Vlek (2009) have suggested that different types of sustainable consumer behaviors are related to various types of causal factors and need to be analyzed separately, some researchers investigate the subject by clustering all types of sustainable behaviors into one behavioral outcome as “pro‐environmental behavior (PEB)” (e.g., Collado et al, 2019; Gatersleben et al, 2002).…”
Section: Introductionmentioning
confidence: 99%